2009
DOI: 10.3168/jds.2008-1399
|View full text |Cite
|
Sign up to set email alerts
|

Impact of postpartum milking frequency on the immune system and the blood metabolite concentration of dairy cows

Abstract: The transition from pregnancy to lactation is marked by metabolic, hormonal, and immunological changes that have an impact on the incidence of infectious and metabolic diseases. The aim of this study was to evaluate the effect on immune function and blood metabolite concentration of limiting milk production in early lactation to reduce negative energy balance. Twenty-two multiparous Holstein cows were milked either once a day (1x) or twice a day (2x) for the first week postpartum. All cows were milked twice da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
87
5
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(101 citation statements)
references
References 34 publications
6
87
5
3
Order By: Relevance
“…This is in accordance with other studies (Dänicke et al, 2012;Renner et al, 2012a and2012b), also observing that the SI changed in the course of lactation. Dairy cows are known to be immune compromised around parturition (Mallard et al, 1998), reflected in an impaired lymphocyte function (Franklin et al, 1991;Goff, 2006) and also in a reduced response of PBMC to mitogen-stimulation (Nonnecke et al, 2003;Loiselle et al, 2009). Consequently, findings indicate a depressed immune function of dairy cows around parturition.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…This is in accordance with other studies (Dänicke et al, 2012;Renner et al, 2012a and2012b), also observing that the SI changed in the course of lactation. Dairy cows are known to be immune compromised around parturition (Mallard et al, 1998), reflected in an impaired lymphocyte function (Franklin et al, 1991;Goff, 2006) and also in a reduced response of PBMC to mitogen-stimulation (Nonnecke et al, 2003;Loiselle et al, 2009). Consequently, findings indicate a depressed immune function of dairy cows around parturition.…”
mentioning
confidence: 91%
“…In particular, little is known about CLA effects on the function of bovine peripheral blood mononuclear cells (PBMCs) during the transition period. Dairy cows are known to have a suppressed immune system in this time (Vangroenweghe et al, 2005), reflected in a reduced response of PBMCs to mitogen-stimulation (Nonnecke et al, 2003;Loiselle et al, 2009). The underlying reasons are not entirely clear, but Lacetera et al (2004) assumed that increased blood non-esterified fatty acid (NEFA) concentrations, as occurring through increased body fat mobilization around parturition, have a negative influence on the function of PBMCs and thus may be responsible for the immunosuppression of transition cows.…”
Section: Introductionmentioning
confidence: 99%
“…The extent of the depression is important and the early PP fall in leptin might play a part (Ingvartsen and Boisclair, 2001). Loiselle et al (2009) milked Holstein cows once or twice daily in week 1 PP and assessed leucocytic cytokine ouput: as expected, leptin levels fell after calving, but less so in cows milked only once daily. Higher INF-g in unmilked cows was consistent with lower immunosuppression, but the study did not prove a causal link to leptin.…”
Section: Leptin and Inflammation And The Immune Responsementioning
confidence: 99%
“…The differences between groups at three stages were not significant, however, increasing rate of glucose level was found slower in T2 than in T1. The plasma glucose concentration was lower in more frequently milked cows (Mc Namara et al 2008;Loiselle et al 2009). High milk yield probably drained plasma glucose into mammary gland for lactose production whereas DMI was not increased to the same extent as milk yield to replace drained glucose during the first three months postpartum, resulting in more severe negative energy balance in more frequently milked cows.…”
Section: Resultsmentioning
confidence: 99%
“…The transition from pregnancy to lactation is marked by metabolic, hormonal and immunological changes that have an impact on the incidence of infectious and metabolic diseases (Loiselle et al 2009). Murphy et al (2005) found that cows milked once daily were in less (P B0.05) negative energy balance than cows milked thrice daily in the early lactation, while Barnes et al (1990) did not observe significant change in mean body weight upon alteration in milking frequency.…”
Section: Introductionmentioning
confidence: 99%